Comportamento suicida em pessoas com trissomia do 21: uma revisão integrativa da literatura - Oliveira, Daniel Galvão de (Universidade Federal de São Carlos, 2023)
Introduction and aim: Trisomy 21 (T21) is a genetically determined condition with an estimated prevalence worldwide of about 1 in every 800 newborns and a documented frequency in Brazil of 1 in 2,785 live births. It consists of a syndrome with multiple forms of expression, whose relationship with the environment and society will define different experiences of being and living for the person with the condition. Clinically, it is characterized by several birth defects, with emphasis on congenital heart defects, which are the most common comorbidity. It is the main genetic cause of intellectual disability (ID) in the world, which is an important manifestation of its phenotypic expression. With the advancement and improvements in care, especially of physical comorbidities, there has been an increase in the discussion about the mental health of individuals with T21, with conflicting evidence about the prevalence of different mental disorders and psychological distress. In this regard, suicidal behavior is an understudied phenomenon in this population, with this review having the objective of answering the question, “What was produced in the specialized literature on the subject ‘suicide in individuals with trisomy 21’?” Methodology: This is an integrative review of studies that deal with the proposed theme, published in English, Portuguese, or Spanish. The search was carried out in three databases: The Virtual Health Library, PubMed, and PsycInfo, using descriptors in English chosen from the "Medical Subject Headings" (MeSH): "Down syndrome", "Down’s syndrome" and "trisomy 21" in combination with "suicide", "suicide, attempted" and "suicidal ideation". The review included articles published until March 10th 2023 and there were no restrictions due to study methodology. The selected studies were evaluated in relation to the level of evidence and classified into thematic categories. Results: Initially, 56 studies were identified, reduced to 32 after excluding articles repeated in different databases. These 32 primary articles were considered based on their titles, abstracts, and writings, resulting in the exclusion of 25 articles that did not concern the subject of the review. Thus, seven articles were selected for full reading, and from the bibliographical references of these seven articles, one more manuscript was included, resulting in a total of eight articles composing this review. Of these, three articles were case reports with or without a narrative literature review, three were narrative literature reviews, and two were cohort studies. The analysis of the articles resulted in four thematic categories: (1) impressions on the production of scientific literature about suicide in individuals with T21; (2) T21 life course elements in the expression of suicidal behavior; (3) frequency of suicide in populations with ID and, more specifically, in individuals with T21; and (4) possible implications for caring for individuals with T21 who may exhibit suicidal behavior. Conclusions: The findings of this review support the notion that the subject has been understudied by the specialized literature, with productions having a low level of evidence in general. However, suicide attempts in individuals with T21 have already been documented, indicating that such a phenomenon is feasible. Epidemiological data are scarce, but two studies included in this review suggest that suicide is less frequent in individuals with T21 than in the general population. New research on the subject is needed to better understand the phenomenon and develop more appropriate diagnostic and therapeutic approaches.
Suicidal behavior in individuals with trisomy 21: an integrative literature review
Keywords: Síndrome de Down; Trissomia do 21; Suicídio; Tentativa de suicídio; Ideação suicida; Revisão; Down syndrome; Trisomy 21; Suicide; Suicide, attempted; Suicidal ideation; Review; CIENCIAS BIOLOGICAS::GENETICA::GENETICA HUMANA E MEDICA; CIENCIAS DA SAUDE::MEDICINA::PSIQUIATRIA; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA